A Modified Advanced Encryption Standard for Color Images - Jassim, Sarah; Hameed, Sarab M. (Iraqi Journal of Science, 2022)
The widespread use of images, especially color images and rapid advancement of computer science, have led to an emphasis on securing these images and defending them against intruders. One of the most popular ways to protect images is to use encryption algorithms that convert data in a way that is not recognized by someone other than the intended user. The Advanced Encryption Standard algorithm (AES) is one of the most protected encryption algorithms. However, due to various types of theoretical and practical assaults, like a statistical attack, differential analysis, and brute force attack, its security is under attack. In this paper, a modified AES coined as (M-AES) is proposed to improve the efficiency of the AES algorithm by increasing the algorithm’s security to make the algorithm more suitable for color image encryption, and make it more resistant to many attacks. The modification is conducted on ShiftRows transformation of the original AES algorithm. To test the efficiency of the proposed M-AES algorithm, several images are drawn from the Signal and Image Processing Institute’s (SIPI) image dataset. Moreover, the Mean Square Error (MSE), Peak Signal-to-Noise Ratio (PSNR), Entropy (H), Correlation Coefficient (CC), visual evaluation of histogram, Number of Pixels Change Rate (NPCR) and Unified Average Changing Intensity (UACI) are used as an evaluation metric. The results show that proposed modiﬁcation to the AES algorithm makes the algorithm more appropriate to image and surpasses the original AES. The modification is conducted on ShiftRows step of the original AES algorithm. To test the efficiency of the proposed M-AES algorithm, several images are drawn from the signal and image processing institute’s (SIPI) image dataset. Moreover, the mean square error (MSE), peak signal-to-noise ratio (PSNR), entropy (H), correlation coefficient (CC), visual evaluation of histogram, number of pixels change rate (NPCR) and unified average changing intensity (UACI) are used as an evaluation metrics. The results show that the suggested modification to AES makes it’s more appropriate to the image and surpasses the original AES.